Komposisi Visual dan Tata Cahaya Pada Film Netflix Berjudul Squid Game - Linando, Stephani Inesia; Prasetyo, Martinus Eko; Winnie, Winnie (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
2021 was the year of Netflix’s sensation, the South Korean drama series,